UMMY SIAPKAN LULUSAN MEMILIKI SOFT SKILL DAN BERDAYA KOMPETITIF: PROGRAM BLPKL TRACER STUDY - Zona Rida Rahayu; Elan Halid; Mega Putri (ASOSIASI IDEBAHASA KEPRI, 2022)
BAN-PT has accredited Universitas Mahaputra Muhammad Yamin (UMMY) Solok, consisting of four faculties and twelve study programs. Ten study programs have received accreditation B, while two have received accreditation C. Since 1984, UMMY Solok has existed. There are 1,800 registered UMMY students until 2022. UMMY Solok graduates roughly 326 students each year for two types of graduations: odd and even semester graduations. It is vital to follow alumni systematically to respond to the growing number of graduates each year. This study attempts to determine the number of UMMY alumni employed, as well as if the knowledge learned during college applies to current jobs. This is geared toward bettering each study program's curriculum to meet the demands of the workplace. The alumni of 2017 graduates, a total of 381 graduates, will be the focus of the tracer study. Manual questionnaires were given to graduates who were not discovered through social media and online questionnaires. Meanwhile, for alumni discovered through social media (via Facebook, line, and WhatsApps) and IT-based, the questionnaires were given on http://www.ummy.ac.id. The questionnaires were given in a more focused and guided way. The establishment of an alumni database for the UMMY Solok tracer research can be accessed through lpkm.ummy@gmail.com. The following are the tracking results: (1) According to the survey results of the tracer study team, UMMY Solok alumni are looking for jobs before they graduate, and the average wait time for a job after graduation is five months. (2) UMMY Solok alumni who have worked in various countries or regions look for work in a variety of ways in order to find positions that match their disciplines and interests. (3) The topic of study is the variety of disciplines researched; the association between the field of study and alumni work is quite close (31,7%). (4) Almost all of the competencies held by alumni are good or very good.